Therapeutic potential of venom peptides: insights in the nanoparticle-mediated venom formulations - Aditya Vivek Joglekar; Deepa Dehari; Md. Meraj Anjum; Naveen Dulla; Aiswarya Chaudhuri; Sanjay Singh; Ashish Kumar Agrawal (SpringerOpen, 2022)
Highlights Nature is an unending and the ultimate source of unique biological compounds which have different pharmacological actions and venom is one of them. Venoms are generally seen as a source of death; however, scientifically venom is a complex biochemical substance having a specific pharmacologic action which can also be used as agents to cure a variety of diseases in humans. Venom peptides along with nanoparticles can evolve as the new era for potential treatments of ongoing and untreatable diseases.